Legal Review of Reporting Opinions and Academic Activities as a Form of Obstruction of Justice - Putri, Maria Sylvia; Harefa, Beniharmoni (PALAR (Pakuan Law review), 2025)
This study examines the legal conflict between constitutional guarantees of freedom of expression, press, and academia with the need to protect the judicial process from obstruction of justice. In the digital age, media narratives and public opinion exert increasing pressure on law enforcement. This study answers two questions: (1) How has the regulation of obstruction of justice developed in Indonesian criminal law? and (2) How are news reports, opinions, and academic activities categorized as forms of obstruction of justice in the investigation process? Using a normative legal method, the study analyzes regulations, legal principles, and case studies. The results show the evolution of regulations from physical offenses in the old Criminal Code (Article 221) to non-physical offenses in the Corruption Eradication Law (Article 21), to systematic codification in the National Criminal Code. The key finding is that the fundamental demarcation lies in proving malicious intent (mens rea) and malicious conspiracy. The Tian Bahtiar case set a precedent that transactional media activities (“obstruction-for-hire”) lose the protection of the Press Law. It is concluded that regulatory ambiguity, especially the phrase “indirectly,” has the potential to create legal uncertainty and a chilling effect that threatens the social control function of the press and academics.